Industrial IoT - Jain, Deepak (Indian Journal of Computer Science, 2021)
This paper discusses industrial internet of things (IIoT), the technologies used, security issues, business use cases and applications in manufacturing operations that are driving the adoption of Industrial IoT in manufacturing